Heterophyllin B, a cyclopeptide from Pseudostellaria heterophylla, enhances cognitive function via neurite outgrowth and synaptic plasticity. (30th July 2021) - Yang, Zhiyou; Zhang, Cai; Li, Xiaohong; Ma, Zhihui; Ge, Yuewei; Qian, Zhongji; Song, Cai
Abstract : Neurite outgrowth‐induced construction of neural circuits and networks is responsible for memory generalization, consolidation, and retrieval. In this study, we found that the traditional Chinese medicine Pseudostellaria heterophylla promoted neurite regrowth and enhanced cognitive function in normal mice. Further, we orally administered Pseudostellaria heterophylla water extracts (PHE) to ICR mice, and detected heterophyllin B (HET‐B), an important cyclopeptide, in the plasma and cerebral cortex. We demonstrated that neurites were significantly elongated after coculturing with HET‐B for 4 days. Next, the intraperitoneal injection of HET‐B on seven consecutive days in 3‐month‐old ICR mice significantly enhanced the object recognition memory and object location memory than that in control. Immunohistochemical analysis indicated significantly increased β3‐tubulin–positive neurite density, synaptophysin, and postsynaptic density 95 in the perirhinal cortex and hippocampus after administering HET‐B. Furthermore, the concentration of neurotransmitters was measured using HPLC analysis; HET‐B significantly increased five‐levels of HT in the hippocampus, and decreased metabolites of dopamine, dihydroxyphenylacetic acid, and homovanillic acid, in the prefrontal cortex and hippocampus. Taken together, HET‐B induces neurite elongation and neurotransmitter regulation and possibly enhances cognitive memory.